Torque movement of the upper anterior teeth using a clear aligner in cases of extraction: a finite element study - Cheng, Yuxun; Gao, Jie; Fang, Shishu; Wang, Wei; Ma, Yanning; Jin, Zuolin (Progress in orthodontics, 2022)
Background Clear aligner treatment has become popular over recent years. It is necessary to identify methods by which we could avoid the bowing effect in extractions with clear aligner. The present study was to identify the appropriate method to design torque movement involving the upper anterior teeth of extraction cases, in order to maintain or improve the axis and torque of the upper anterior teeth with a clear aligner during movement and closure of the extraction space. Results As the height of the power ridge increased, the rotation angle of the upper central incisor in the sagittal direction decreased gradually and the location of the rotation center changed significantly; the rotation center moved in the apical direction and then changed to the crown side. The highest von-Mises stress of the upper central incisor root, periodontal ligaments, and alveolar bone, showed little change as the power ridge height increased. When the axial inclination of the upper central incisor was normal (U1-SN = 105°), the tendency of movement for the upper central incisor approached translation with a power ridge height of 0.7 mm (corresponding distorted angle: 5.8415). When the axial inclination of the upper central incisor was oversized (U1-SN = 110°), the axial inclination of the upper central incisor reduced to normal following completion of the anterior segment retraction with a power ridge of 0.4 mm (corresponding distorted angle: 3.4265). Conclusion Analysis indicates that pure palatal tipping movement of the upper anterior teeth is generated without torque control, thus resulting in the bowing effect. The required torque control of the upper anterior teeth with oversize axial inclination is weaker than that of the upper anterior teeth with normal axial inclination because limited torque loss is expected for oversize axial inclination teeth . Variation sensitivity of the rotation center should be considered carefully due to biological problems when designing translation of the upper anterior teeth with normal axial inclination.